UJI BERBAGAI JENIS BAHAN MATRICONDITIONING TERHADAP VIABILITAS DAN VIGOR BENIH PADI (ORYZA SATIVA L.) VARIETAS INPARI 32: TEST OF VARIOUS TYPES OF MATRICONDITIONING MATERIALS ON THE VIABILITY AND VIGOR OF RICE SEEDS (ORYZA SATIVA L.) INPARI 32 VARIETIES - Suparto, Hairu; Widyawati, Wahyu (Fakultas Pertanian Universitas Palangka Raya, 2024)
The aim of this research was to determine the type of matriconditioning material on the viability and vigor of rice seeds of the Inpari 32 variety. The research was carried out in April – June 2024 at the Agroecotechnology Integrated Laboratory, Faculty of Agriculture, ULM. The research used a single factor Completely Randomized Design (CRD), namely treatment type matriconditioning consisting of: m0: control (water); m1: Husk charcoal; m2: Rubbing ash; m3: Sawdust; m4: Charcoal husk & Ash (1:1); m5: Husk charcoal & sawdust (1:1); m6: Crushed ash & Sawdust (1 : 1) and m7: Husk charcoal & Crushed ash & Sawdust (1:1:1). The results of the research showed that the treatment had no real effect on the maximum growth potential of the seeds, but had a significant effect on the germination capacity, simultaneous growth and growth speed of the rice seeds of the Inpari 32 variety. The best treatment was sawdust matriconditioning material which was able to increase the viability and vigor of the rice seeds. Inpari 32